PENGARUH KOMPETENSI PEDAGOGIK TERHADAP KINERJA GURU DIMODERASI IKLIM ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH (Studi Guru SMK Negeri se Kabupaten Kendal) - Oktivani, Ika; Basiya, R. (Jurnal Ilmiah Telaah Manajemen, 2018)
This study to examine the influence of Pedagogic Competence on Teacher Perfomance moderated Organizational Climate and Principal Leadership (Studies on SMK Negeri Teachers Kendal District). This research is included into quantitative research by using technique through descriptive analysis approach. This research uses census technique where the number is equal to the total population of 211 teachers, and data are processed also as many as 211 teachers. Measurement using Likert scale with 5 (five) alternative answers. The instrument test used is the validity test and the reliability test and the classical assumption. For model test using Coefficient of Determination, F test, and T test as hypothesis test, so this research use regression analysis. Based on the result of the research, it can be concluded that Pedagogic Competence has positive and significant effect on Teacher Performance, Organizational Climate has positive and significant impact on Teacher Performance,Principal Leadership has positive and significant impact on Teacher Performance,Organizational Climate not moderating the Influence of Pedagogical Competence on Teacher Performance,Principal Leaders Moderate the Influence of Pedagogical Competence on Teacher Performance to employee performance, and motivation variable strengthens the relationship between organizational commitment variable to employee performance Nissan Service Center Semarang City. Keywords: Pedagogic Competence, Organizational Climate, Principal Leadership, Teacher Performance.